CHINA DEFEATS CORONAVIRUS IN 60 DAYS AND BUILDS GLOBAL SANITARY SILK ROAD. WHAT’S NEXT? - Dieterich, Heinz (ВЕСТНИК ЧЕЛЯБИНСКОГО ГОСУДАРСТВЕННОГО УНИВЕРСИТЕТА, 2022)
-   DOI:  https://doi.org/10.24411/1994-2796-2020-10225